Cholangiography in liver trauma: This work won the Hoechst Prize at the Forum of the XXVIII Uruguayan Congress of Surgery - Villar, Miguel; Martinez, Jorge; Veroli, Antonio; Artigalas, Raúl; de León, Luis (Cirugía del Uruguay, 1978)
The results of operatory cholangiog· raphy in 15 experimental cases of liver traumatisms are analyzed in this paper. In three situations the existence of deep ]esions were not suspected on the basis of superficial lesions; cholangiography made them evident and they were confirmed by anatomopathology. The value in our country of this simple and practica! method of diagnosis, appears evident when compared with other more sophisticated studies.